(untitled) (European Journal of Education, 2021)
This study aimed at investigating the mediating effect of creative thinking on multiple-intelligence and thinking patterns among 10th-grade students in Abu Dhabi private schools. This study used descriptive approach and SEM. Also, the study sample consisted of 350 students from five private schools in Abu Dhabi. The instruments used were Gardner’s multiple-intelligence scale and thinking patterns scale. Data was analysed using descriptive statistics, correlation coefficient and Amos. The results showed significant positive relationship between multiple intelligences (IV) and thinking patterns (DV) through creative thinking (MV). Direct significant positive relationships were found between interpersonal intelligence (IV) and thinking patterns (DV) (r=.241); natural intelligence (IV) and thinking patterns (DV) (r=.113); musical intelligence (IV) and thinking patterns (DV) (r=.000); bodily-kinaesthetic intelligence (IV) and thinking patterns (DV) (r=.000). In conclusion, the findings revealed the influence of creative thinking on the relationship between multiple-intelligence and thinking patterns.